Automatic Personal Identification System for Security in Critical Services: Two Case Studies based on a Wireless Biometric Badge - Tennina, Stefano; Pomante, Luigi; Tarquini, Francesco; Graziosi, Fabio; Santucci, Fortunato (IntechOpen, 2011)
None